Panduan Transformasi Produk Budaya Menjadi Produk Kreatif Budaya Melalui Model Map (Studi Kasus Topeng Malangan) - Erik Armayuda; Reven Praga Deva (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Culture is one source of inspiration that will be a key value of product competition in the global market. Indonesia with more than 1,300 different ethnic groups has cultural richness which will be the key differentiator in the global market. As the development of the creative industry, culture becomes an element that has more value. There are so many potential cultural products that can be explored. Each requires a study of different approaches to extracting cultural values ​​in a product. From the skin "outside", "content", to "spirit" which is the core of the culture. By using transformation methods in cultural products to assess three levels of cultural features; outside, middle, and inside, this research is expected to provide appropriate exploration in cultural identification especially at the "outside" level. This paper will focus on the Malangan mask culture originating from the city of Malang, East Java. This study proposes guidelines for changing culture and provides alternative product development that can provide guidance for turning cultural products into creative products of culture in an effort to make it more adaptive in the current era.